ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI PERTUMBUHAN PRODUK DOMESTIK REGIONAL BRUTO ERA DESENTRALISASI FISKAL DI PROPINSI BANTEN PERIODE 2001:1-2009:4 - Hendry Sulaiman Nasution (Media Ekonomi, 2010)
The purpose of this study was to determine the factors that affect economic growth in the Province of Banten. This research was using the multiple linear regression analysis which is used to measured the pattern of the relationships between dependent variable and independent variables. The variable GRDP is a dependent variable and the independent variable are Income Original Region, General Allocation Fund, Fund Devide Result, Inflation, Foreign Investment, Domestic Investment, Government Spending and Labor. The estimation result of this model, showed that from 8 variables, there were 3 variables that insignificant which were inflation, foreign investment and domestic investment to influenced GRDP Province of Banten. Another five variables which were : Income Original Region, General Alocation fund, Fund Devide Result, Government spending and labour that significant to influenced GRDP. In the other hand, Goodness of fit of this model had a value of R² were 0,9867. From thismodel about 98,67% the Independent variables Income Original Region, GeneralAllocation Fund, Fund Devide Result , Inflation, Foreign Investment , DomesticInvestment, Government Spending and Labor expalained the relationship to GRDP of Banten. And about 1,32% will be explained by another variables that not obtained in this model.